2014
DOI: 10.1186/1748-717x-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy combined with intracerebral administration of carboplatin for the treatment of brain tumors

Abstract: BackgroundIn this study we determined if treatment combining radiation therapy (RT) with intracerebral (i.c.) administration of carboplatin to F98 glioma bearing rats could improve survival over that previously reported by us with a 15 Gy dose (5 Gy × 3) of 6 MV photons.MethodsFirst, in order to reduce tumor interstitial pressure, a biodistribution study was carried out to determine if pretreatment with dexamethasone alone or in combination with mannitol and furosemide (DMF) would increase carboplatin uptake f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
1
23
1
1
Order By: Relevance
“…Our median survival times of rats treated with carboplatin were generally shorter than those reported by the teams of Elleaume and Barth. For example, MeST of 45 days and 43 days were obtained respectively by Rousseau J. et al [13] and Yang W. et al [20], while only 38.5 days was observed in our study when treated with carboplatin. The differences may be due to the following reasons.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Our median survival times of rats treated with carboplatin were generally shorter than those reported by the teams of Elleaume and Barth. For example, MeST of 45 days and 43 days were obtained respectively by Rousseau J. et al [13] and Yang W. et al [20], while only 38.5 days was observed in our study when treated with carboplatin. The differences may be due to the following reasons.…”
Section: Discussionsupporting
confidence: 44%
“…Additionally, a phase I clinical trial showed that it was safe and feasible to deliver carboplatin by CED to treat glioblastoma [18]. However, due to the large diversity of the techniques, animal models, and/or drug dosages used in different studies [12,13,19,20], it is unclear if the CED of one particular platinum-based antineoplastic agent is better than the others. Moreover, it is paramount to evaluate the liposomal formulations of platinum drugs and compare their performance to that of free platinum drugs, particularly since it has been reported that liposomal chemotherapy drugs delivered by CED have longer retention times in the tumor area, and can further extend survival [21].…”
Section: Introductionmentioning
confidence: 99%
“…114 This method was pioneered by Neuwelt and colleagues in 1979, 119 and the effectiveness of a 25% mannitol solution was investigated in clinical trials in 1981. 120 Further analysis in rat models indicated that this disruption of the BBB is maintained for approximately 30 minutes 82,179 and that permeability is achieved for between 15 minutes and 4 hours, depending on the molecular weight of the agent used. Current in vivo research efforts involve intraarterial injection of the hyperosmotic agent that induces BBB disruption and subsequent intraarterial injection of the drug of interest.…”
Section: Hyperosmotic Disruptionmentioning
confidence: 99%
“…В последнее время появляются данные о положи-тельном результате при предварительном облуче-нии головного мозга с опухолями перед химиотера-пией, однако диапазон применяемых доз фракцио-нированной радиотерапии довольно широк [4][5][6]. К примеру, большинство исследователей [7][8][9] счи-тают, что лучевая терапия в дозах от 20 до 30 Гр с размером фракции 2 Гр может применяться для прорыва ГЭБ без особых побочных эффектов.…”
unclassified